Foot pressure profile for the paretic and non-paretic lower extremities in children with spastic hemiplegic cerebral palsy and the relationship with postural stability. Cross-sectional study - Alruwaili, Atheer; Ibrahim, Alaa; Abualait, Turki (Acta Biomedica Atenei Parmensis, 2025)
Background: Cerebral palsy is a nonprogressive neurodevelopmental disorder that causes motor impairments and limb asymmetries in children with hemiplegic CP, leading to altered plantar pressure, reduced postural stability, and functional gait limitations.Aim: This study compared foot pressure profiles between paretic and non-paretic limbs in children with hemiplegic cerebral palsy and controls and examined their relationship with postural stability.Methods: In this cross-sectional study, 20 children with HCP (mean age: 8.1±1.65 years) and 31 TD (mean age: 8.06±1.15 years) underwent spasticity assessment using the Modified Ashworth Scale. Static plantar pressures were measured with the DIERS Pedoscan system, while dynamic PS indices were recorded using the TecnoBody device under eyes-open and closed conditions.Results: Within the HCP group, affected feet demonstrated significantly lower maximum and average pressures, pressure distribution, surface area, and hindfoot pressure compared to non-affected feet (all p≤0.019). Compared to controls, children with HCP showed significantly greater limb length discrepancies (p